Studies on Zinc(II)-Biosorption Capability of a Filamentous Green Algal Species (Mougeotia viridis) Isolated from Electroplating Wastewater (Biological Sciences - PJSIR, 2006)
The biosorption capacity of zinc(II) by a filamentous green alga Mougeotia viridis, isolated from the waste- water discharged by electroplating industry was tested under laboratory conditions as a function of contact time, pH, and initial metal ion and biomass concentrations. Optimum pH value for zinc(II) biosorption was determined as 5.0. At 10 mg l-1 zinc(II), the biosorption equilibrium with 1 g l-1 algal biomass was reached in 10 min showing a relative efficiency of 59.24% metal removal. When the biosorbent biomass was increased to 2 g l-1, the metal removal capacity was enhanced to 81.4%. At optimum conditions, zinc(II) uptake increased with the increase in initial metal ion concentration from 5-300 mg l-1. Langmuir isotherm model was found to be suitable for describing the biosorption of zinc(II) by Mougeotia viridis. The q obtained experimentally and theoretically calculated from the Langmuir isotherm model at the regression coeffi- cient value of 0.9975, respectively, were 27.7 mg and 26.71 mg zinc(II) g-1 algal biomass, at the initial metal concentration of 200 mg l-1. In five repeated biosorption-desorption cycles, the zinc(II) desorption from the metal-loaded algal biomass remained around 99%. The observations reported in the present study indicate that the alga can be used as an efficient biosorbent for the removal of zinc(II) from aqueous solution.